Legal Protection for Child Victims of Bullying from the Perspective of Child Protection Law - Mayasari, Dian Ety; Atjengbharata, Andreas L.; Seguito Monteiro (Universitas Airlangga, 2024)
Legal protection for children has not been effective and there are still children who are victims of bullying. Bullying is an action that hurts the victim both physically and psychologically. The occurrence of bullying is a form of violation of children's rights which is regulated in the Child Protection Law, so perpetrators must be dealt with firmly by imposing criminal sanctions which are also regulated in the Child Protection Law. The purpose of this writing is to find out legal protection for children who are victims of bullying, especially repressive legal protection. It uses a normative juridical method that prioritizes primary legal material of the Child Protection Law. The final result is that the regulation of criminal sanctions in the Child Protection Law is cumulative and there are regulations for minimum and maximum criminal threats, so that judges in giving decisions on criminal sanctions can be minimal. This lack of firmness in setting sanctions does not provide a deterrent effect for perpetrators and other people who continue to carry out bullying actions against children.